Reinforcing Effect of Carbon Nanotubes/Surfactant Dispersions in Portland Cement Pastes - Oscar A. Mendoza Reales; Caterin Ocampo; Yhan Paul Arias Jaramillo; Juan Carlos Ochoa Botero; Jorge Hernán Quintero; Emílio C. C. M. Silva; Romildo Dias Toledo Filho (Advances in Civil Engineering)
Decoupling the individual effects of multiwalled carbon nanotubes (MWCNTs) and surfactants when used as reinforcement materials in cement-based composites is aimed in this study. Powder MWCNTs were dispersed in deionized water using different types of surfactants as chemical dispersing agents and an ultrasonic tip processor. Cement pastes with carbon nanotubes additions of 0.15% by mass of cement were produced in two steps: first, the MWCNT/surfactant dispersions were combined with the mixing water, and then, cement was added and mixed until a homogeneous paste was obtained. Mechanical properties of the pastes cured at 7 days were measured, and their fracture behavior was characterized using the linear elastic finite element analysis. It was found that the reinforcing effect of MWCNT was masked by the negative effect of surfactants in the cement matrix; nevertheless, nanotubes were capable of increasing both stress and strain capacity of the composite by controlling the crack propagation process at the tip of the crack.